Chronic Respiratory Symptoms and Lung Function of Farmer and Breeder in UTU Village, Tabanan, Bali - Arisanti, Ni Luh Putu Eka; Widiasari, Ni Putu Ayu; Rai, Ida Bagus Ngurah (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The objective of the study was to determine chronic respiratory symptoms and lung function of farmers. METHODS: The study was conducted in Utu Village, Tabanan, Bali with 84 subjects. This research was observational analytic cross sectional study. RESULTS: Three dominant chronic respiratory symptoms in farmers were coughing (15.1%), dyspnea (13.1%), and phlegm (13.1%). Average values of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and FEV1/FVC were 83.75 ± 34.42, respectively, 81.62 ± 34.30 and 104.90 ± 13.90, respectively. Cough was dominant experiencing by smokers (p = 0.008). Mean of FEV1% prediction and FVC% prediction value was lower in passive smoker group than no smoker group (p = 0.005 and p = 0.03). CONCLUSION: Occupational exposure while farming and raising livestock can cause chronic respiratory symptom and lung function decline in farmers and can be influenced by smoking history and secondhand smoke exposure.